2008
DOI: 10.1002/marc.200800279
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Anisotropic Polymer Particles with Soap‐Free Emulsion Polymerization in the Presence of a Reactive Silane Coupling Agent

Abstract: A novel two step method has been developed for the preparation of anisotropic polymer particles using soap‐free emulsion polymerization in the presence of the reactive silane coupling agent 3‐methacryloxypropyltrimethoxysilane (MPTMS). In the first step, seed polymer particles were prepared in the presence of MPTMS in water. In the second step, another polymerization was conducted in the presence of the seed particles, which induced anisotropic protrusion of polymer from the seed particles. The two step method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 24 publications
(18 reference statements)
0
64
1
Order By: Relevance
“…1,2 Additionally, a body-centered orthogonal crystal phase is observed for intermediate field strength and density in the case of soft repulsive spheres. [1][2][3] The phase behaviour of anisotropic colloidal particles, such as rods, [4][5][6] dumbbells, 7-9 snowman particles, 10,11 and bowls, 12,13 has received significantly less attention, even though great progress has been made in the synthesis of such particles in recent times (see, e.g., Ref. 14).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Additionally, a body-centered orthogonal crystal phase is observed for intermediate field strength and density in the case of soft repulsive spheres. [1][2][3] The phase behaviour of anisotropic colloidal particles, such as rods, [4][5][6] dumbbells, 7-9 snowman particles, 10,11 and bowls, 12,13 has received significantly less attention, even though great progress has been made in the synthesis of such particles in recent times (see, e.g., Ref. 14).…”
Section: Introductionmentioning
confidence: 99%
“…In the approach of seeded emulsion polymerization, crosslinking of the seed particles is generally assumed a prerequisite for the formation of non-spherical shapes, although it is recently reported that core-shell structured seed particles with a dense inorganic or a cross-linked shell and a non-cross- Table 1 excited by an excitation light of 263 nm linked core may be an effective route as well [51,52]. We investigated the non-cross-linked RNP-2 as the seeds and found that hollow nanocomposite particles can be obtained instead of snowman-like Janus particles (Fig.…”
Section: Characterization Of Sjp Obtained By Seeded Emulsion Polymerimentioning
confidence: 99%
“…Magnetic core nanoparticles were synthesized as previously described [5]. Styrene (24.0 mmol), MPDMS (0.52 mmol), MTR (0.048 mmol), and KPS (0.64 mmol) were added to 40 mL of an acetate buffer solution.…”
Section: Preparation Of Magnetic Core Nanoparticlesmentioning
confidence: 99%